Methodology of properties protyspratsovuvalnyh lubricants by tryboharakterystyk formed in their secondary structures - Аксьонов, О.Ф.; Стельмах, О.У.; Шимчук, С.П.; Коба, В.П.; Мансур, Джамаль Ібрагім (Proceedings of National Aviation University, 2006)
The methodology of construction the laboratory methods of definition the antiwear properties of materials by the criteria of tribological properties of the secondary structures which are formed in the corresponding oils is offered.